Chitosan-grafted-polyaniline copolymer as an electrically conductive and mechanically stable binder for high-performance Si anodes in Li-ion batteries. (10th February 2020) - Rajeev, K.K.; Kim, Eunsoo; Nam, Jaebin; Lee, Suhyun; Mun, Junyoung; Kim, Tae-Hyun
Abstract: We developed chitosan- grafted -polyaniline copolymers (CS- g -PANIs) as new water-soluble electrically conductive and mechanically robust polymer binder materials for silicon anodes. Unlike most other electrically conductive polymer binders, the CS- g -PANIs were easily prepared by grafting electrically conductive PANI onto the chitosan, which adheres well to Si. Various CS- g -PANI copolymers were prepared with different grafting degrees of PANI to investigate the effect of PANI on the electrochemical and physical properties of the prepared electrodes. The copolymer whose composition was 50% PANI and 50% chitosan showed the best cell performance, due to the well-balanced electrical conductivity and mechanical properties. It exhibited a specific capacity of 1091 mAh g −1 at the 200th cycle with 99.4% Coulombic efficiency. Graphical abstract: Image 1